Women's International League for Peace and Freedom At Courthouse Transit Stop Protesting Removal From Buses Their "Think Before You Register For The Draft" Signs - Watkins, Howard::::::::: (1982)
Channel 24 cameraman and reporter Jack Noldon and other reporters interviewing Sandra Iyall about protest; Connie Petersen in background Women's International League for Peace and Freedom banner and banned posters in background